Analysis of Ilmu al-Ma‘ani and Indonesian Language Styles: Students Perpective: التحليل التقابلي بين مباحث علم المعاني وأساليب اللغة الإندونيسية من منظور طلاب الجامعة - Ridho, Rosyid (Langkawi: Journal of The Association for Arabic and English, 2025)
Although many studies have examined the contrastive analysis of Ilmu Ma'ani in Arabic and Indonesian styles, few have analyzed it from the perspective of students at Islamic universities in Indonesia. Therefore, this study aims to examine students' perceptions of Islamic universities in Indonesia regarding the comparison between Islamic science in Arabic and Indonesian styles. Using the theory of Sheikh Ahmad bin Abdurrahman ad-Damanhuri in Arabic and the theory of Jusuf Sjarif Badudu in Indonesian, along with content analysis and unstructured interviews, the results of this study show that (1) there are similarities between the eight chapters in ma'ani science and the eight discussions in Indonesian language style, including isnad, which is similar to a clause, musnad ilaih which is similar to the subject, musnad which is similar to the predicate, muta'alliqatul fi'li which is similar to the object, al-qashr which is similar to the contradiction interminus, al-insya' (al-amr, al istifham and al tamanni) which is similar to the interactive, interrogative, assumption, al-washl and al fashl which are similar to sidenton, asidenton, and al-ithnab, al-jaz and al musawah which are similar to ellipsis, redundancy (2) Students' perceptions show that the discussion of ma'ani in Arabic is similar to the discussion of Indonesian style. Indonesian in terms of definitions and examples, but in both discussions, there are very significant differences in terms of division, application in text, and depth of discussion, including the clarity of Arabic sentence meaning and the existence of Arabic sentences that cannot be adequately represented by Indonesian, either in translation or in rules. The results of this study imply that the eight chapters in ma'ani science have equivalents in Indonesian stylistics, but there are also differences between the two discussions because they originate from two different languages.